Fabrication of multi-component nanomaterials in colloidal solution - Wang, Yong (2012)
This thesis focused on the fabrication of multi-component nanomaterials in colloidal solution. The optical properties of these novel structures also have been studied. Multi-component nanostructures usually have abundant structural variety. They can provide not only the properties of each individual, but also the new feature originated from the interaction of them. Therefore, insight into the multi-component system may offer new synthetic strategies and novel architectures, satisfying the requirement of future nanodevices. Two strategies have been adopted for the fabrication of multi-component nanomaterials in this dissertation: rational assembly of nano-objects; direct synthesis based on wet chemistry.